DNA‐based approaches for evaluating historical demography in terrestrial vertebrates. (15th April 2014) - Fahey, Anna L.; Ricklefs, Robert E.; Dewoody, J. Andrew
<x xml:space="preserve">Abstract</x> Contemporary DNA sequences can provide information about the historical demography of a species. However, different molecular markers are informative under different circumstances. In particular, mitochondrial (mt)DNA is uniparentally inherited and haploid in most vertebrates and thus has a smaller effective population size than diploid, biparentally inherited nuclear (n)DNA. Here, we review the characteristics of mtDNA and nDNA in the context of historical demography. In particular, we address how their contrasting rates of evolution and sex‐biased dispersal can lead to different demographic inferences. We do so in the context of an extensive review of the vertebrate literature that describes the use of mtDNA and nDNA sequence data in demographic reconstruction. We discuss the effects of coalescence, effective population size, substitution rates, and sex‐biased dispersal on informative timeframes and expected patterns of genetic differentiation. We argue that mtDNA variationin species with male‐biased dispersal can imply deviations from neutrality that do not reflect actual population expansion or selection. By contrast, mtDNA can be more informative when coalescence has occurred within the recent past, which appears to be the case with many vertebrates. We also compare the application and interpretation of demographic and neutrality test statistics in historical demography studies. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 367–386.